2002
DOI: 10.1038/sj.bjc.6600016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MAGE-1 and MAGE-3 as tumour-specific markers to detect blood dissemination of hepatocellular carcinoma cells

Abstract: The members of MAGE gene family are highly expressed in human hepatocellular carcinoma (HCC). In the present study, we tested the tumour-specific MAGE-1 and MAGE-3 transcripts in the peripheral blood of HCC patients by nested RT -PCR to detect the circulating tumour cells and evaluate their potential clinical implication. Of 30 HCC patients, the positive rate of MAGE-1 and MAGE-3 transcripts was 43.3% (13 out of 30) and 33.3% (10 out of 30) in PBMC samples, whilst the positive rate was 70% (21 out of 30) and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 28 publications
5
62
0
Order By: Relevance
“…Our previous reports also indicated that blood dissemination of tumor cells occurred in the early stage of HCC. 35 Detection of the FATE/BJ-HCC-2 gene transcript in PBMCs by nested PCR may be useful for specifically diagnosing micrometastasis of HCC cells in peripheral blood and benefit the prediction of HCC recurrence and prognosis of the disease after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous reports also indicated that blood dissemination of tumor cells occurred in the early stage of HCC. 35 Detection of the FATE/BJ-HCC-2 gene transcript in PBMCs by nested PCR may be useful for specifically diagnosing micrometastasis of HCC cells in peripheral blood and benefit the prediction of HCC recurrence and prognosis of the disease after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of metastatic tumor cells is critical to identify HCC patients at high risk of relapse and for the prescriptive therapy. 35 Since Smith et al 36 first successfully adopted the RT-PCR technique to assess tyrosinase mRNA as a tumor marker to detect circulating melanoma cells, the gene transcripts of both tissueassociated and tumor-specific markers have been applied in RT-PCR-based diagnosis of micrometastasis of tumor cells in peripheral blood, such as the tyrosinase and MAGE-3 transcripts in melanoma, MAGE-1 and MAGE-3 in HCC, etc. [35][36][37][38][39] The results in this study showed that the FATE/BJ-HCC-2 gene transcript was positive in PBMCs of 46.67% patients whose resected HCC tumor tissues were positive for FATE/BJ-HCC-2, implying the early dissemination of HCC cells in blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…As shown the Fig 1 and Tab 2, although some samples were homozygously methylated or unmethylated, the majority had the co-existed methylated and unmethylated alleles. Inclusion of the normal liver tissues in our study enabled us to establish the normal methylation pattern of all the forty four genes, that except for the MAGEA1 [31] being homozygously methylated, the rest forty three were homozygously demethylated [27] (Fig 1 and Tab 2). Therefore, any changes in the methylation pattern from the normal liver tissue's to the non-cancerous neighboring tissues or HCC tissues should indicate the involvement of the DNA methylation mediated events during the HCC carcinogenesis, that have been scored as the positive methylation change.…”
Section: Methylation Profilingmentioning
confidence: 99%
“…Therefore, we have also assessed whether the switching-on of the otherwise hypermethylated genes in the normal cells is linked to the demethylated state of the promoter CpG island in the HCC tissues. The MAGEA1 gene is such an example, expression of which is off in the normal hepatocytes and on in HCC [31]. Correlating well with such an expression profile, we in deed found that the promoter CpG island of the MAGEA1 (panel 13, Fig 1) was fully methylated in the normal liver tissue, became unmethylated at a similar frequency in 18/28 (64%) and 21/28 (75%) in each of the paired HCC tissue samples, respectively.…”
Section: Hypomethylation Of the Promoter Cpg Island Of The Magea1 Genmentioning
confidence: 99%
“…It has been reported that the simultaneous determination of p53 antigen and anti-p53 antibodies has a sensitivity of 41.1% in the diagnosis of HCC [52] , and the over-expression of p53 in the serum or liver tissues of HCC patients prefigures the poorer prognosis and a shorter survival time (P = 0.0014) [52][53][54][55][56] . HCC patients with positive MAGE-1 or MAGE-3 mRNA die earlier because of metastasis or recurrence [57] . The sensitivity and specificity of serum human cervical cancer oncogene (HCCR) at the cut-off value of 15 µg/mL in detecting HCC are 78.2% and 95.7%, respectively.…”
Section: Genesmentioning
confidence: 99%